The Effect of Experimental Methods on Science Ability in Children Aged 5-6 Years at Paud Rafflessia Arnoldy Kayu Tiga, Sirimau District, Ambon City (International Journal of Education, Information Technology, and Others, 2023)
The experimental method will provide opportunities for children to gain direct and enjoyable learning experiences. Thus encouraging children to be skilled in doing their own experiments. In the process of teaching and learning with the experimental method, children are also given experience to observe an object by themselves. Thus the child is required to experience it for himself, seek the truth, look for the necessary data, obtain the data himself, prove a law and draw conclusions from the process he is experiencing. This is in accordance with Djamarah and Zain (2010: 84) which states that the experimental method is a learning method in which students are required to experience it for themselves, seek the truth, or try to find a law or truth and draw conclusions from the process they experience. This study aims to determine the effect of the experimental method on the ability of science in children aged 5-6 years at Rafflessia Arnoldy Kayu Tiga Early Childhood Education, Sirimau District, Ambon City. In this study using a quantitative descriptive method. The research method used is quasi-experimental research methods or (like an experiment). The results of this study indicate that there is an effect of the experimental method on increasing the ability to learn science after using the experimental method in children aged 5-6 years at Rafflessia Arnoldy Kayu Tiga Early Childhood Education. This is evidenced by the distribution table of scientific abilities in early childhood children after using the experimental method which is in the range of scores from 0 to 100 and the lowest score is 13, while the highest score is 20, obtained an average of 16.66.